OC27 National newborn screening for cystic fibrosis: genetic data from the first 6 years. (June 2019) - Sasaki, Erina; Kostocenko, Marija; Lang, Niamhe; Clarke, Tara; Rogers, Melissa; Muldowney, Rebecca; Ward, Alana; Barton, David; Lynch, Sally Ann
Abstract : Background: Cystic Fibrosis (CF) is the most common life threatening autosomal recessive multisystem disease in the Republic of Ireland (ROI); with a previously quoted incidence of 1 in 1353 and carrier rate of 1 in 19. Screening for CF was incorporated in the National new born screening (NBS) programme in July 2011 in the ROI. The benefit of early diagnosis is well documented. The purpose of the screening is to identify classic CF cases to allow early diagnosis and intervention and improve prognosis. A cut off point of the top 1% Immunoreactive Trypsinogen (IRT) was taken as an indication for 38 mutation panel molecular screening in the ROI National screening programme to maximise identification of affected typical CF cases and to minimise detection of carriers. Methods: All neonates from July 2011 to Dec 2017 who had an elevated IRT on NBS were tested with 38 CFTR gene mutation panel and included in this study. Data from clinical and laboratory database were analysed and cross-referenced with patient charts. The Non-NBS database was used to track down cascade relatives. Results: In the first 6 and a half years a total of 5, 094 newborns (1.16% of total births in the period) were screened for CFTR mutation. During this period, 170 CF affected cases, 22 CFSPID (CF screening positive, Inconclusive diagnosis) and 325 healthy carriers were identified. Phe508del was the most common mutation (75%) followed by Gly551Asp (9.4%). 95 (56%) were homozygous for Phe508del, 17 (10%) were compound heterozygous for Phe508del and Gly551Asp and 22 (13%) were compound heterozygous for Gly551Asp. Hence, 69% of identified as an affected new-borns are eligible to use orphan drugs. There was one missed diagnosis. Conclusion: The National new-born screening programme has been successful with only 1 missed diagnosis and less than 50% of carriers identified than predicted. We identified twice the number of affected new-born carrying the Gly551Asp mutation than previously quoted figures from elsewhere in Western Europe. As these are eligible for new orphan drugs this is important for drug reimbursement nationally. The revised incidence of CF in the ROI is less than previous reports (likely due to net immigration). We estimate the new revised incidence to be 1 in 2570 and the carrier frequency is 1 in 25.